2007
DOI: 10.1080/01612840701354612
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and Carer Participation in Mental Health Care: The Carer's Perspective: Part 2—barriers to Effective and Genuine Participation

Abstract: Family members and significant others provide significant proportions of unpaid care for people experiencing a mental illness. Although the carer role is pivotal to contemporary mental health service delivery, the role of carers and the issues they face have received only scant attention in the literature. This paper presents the second part of the findings of an exploratory, qualitative inquiry, which sought greater understanding of carers' experiences of, and attitudes to opportunities for participation in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 15 publications
(11 reference statements)
1
29
1
Order By: Relevance
“…Nevertheless, it seemed to them that carers’ voices in relation to individual patients were being heard more than in the past. Similar to other studies (Goodwin & Happell 2007b, Lakeman 2008), practical barriers such as geographical dispersal impacted significantly for those carers residing across Scotland who were trying to maintain involvement with individuals held at the State Hospital.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Nevertheless, it seemed to them that carers’ voices in relation to individual patients were being heard more than in the past. Similar to other studies (Goodwin & Happell 2007b, Lakeman 2008), practical barriers such as geographical dispersal impacted significantly for those carers residing across Scotland who were trying to maintain involvement with individuals held at the State Hospital.…”
Section: Resultssupporting
confidence: 60%
“…Despite agreement among commentators about the benefits of involving carers at policy level (Cleary et al. 2005, Hayman & Fahey 2007), and at the individual level (Goodwin & Happell 2007a,b, Lakeman 2008), practice continues to fall short. More recently, Gray et al.…”
Section: Discussionmentioning
confidence: 99%
“…Many published papers discuss the challenges associated with professional / carer relationships and which impact upon the extent to which carers are involved in practice. The theme of 'conflicting agendas' has been used, for example, in relation to the communication observed between informal caregivers and mental health staff in Australia [18,19]. Carers in their study discussed limited opportunities for them to participate in planning support for the person that they supported.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also suggest that psychoeducational interventions should consider gender differences and family roles. In Australia, Goodwin and Happel 142,143 found that family members and significant others contribute to the smooth delivery of care and treatment, particularly when they feel respected and are included in communications, but the researchers also observed a lack of discussion regarding carer participation in health care delivery.…”
Section: Family and Carers: Needs And Preferencesmentioning
confidence: 99%